ADAM: An Autonomous Agent for High-Frequency Currency Trading in the Brazilian Market - Zuffo, Vicente Matheus M.; Castro, Paulo André L. de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2012)
This paper presents an autonomous system called ADAM (Autonomous Dollar futures Agent Model) that implements a strategy based in the “Follow The Leader” concept to trade liquid futures contracts in the Brazilian exchange BM&F, taking in consideration peculiarities of the respective market. The agent operates at high frequency, being one of the first of its kind in this market.